Healing Families: Outcomes from a Family Drug Treatment Court. (June 2016) - van Wormer, Jacqueline; Hsieh, Ming‐Li
Abstract: Family drug treatment courts (FDTC) have been acknowledged as a promising intervention for substance‐abusing parents involved in the child welfare system. Over the past decade, the number of FDTC programs has grown substantially, yet questions remain regarding the efficacy of these courts. This study examines the ability of the Snohomish County (WA) FDTC to address the three main goals of the Adoption and Safe Families Act. Utilizing propensity score matching, this study found that participants were more likely to have their children returned, experienced stronger treatment completion rates, and had less use of foster care. Implications for replication and further analysis are discussed.